COVID-19 Outbreak on Environment: Profile of Islamic University Students in HOTS-AEP-COVID-19 and PEB-COVID-19 - Ichsan, Ilmi Zajuli; Rahmayanti, Henita; Purwanto, Agung; Sigit, Diana Vivanti; Irwandani, Irwandani; Ali, Ahmad; Susilo, Susilo; Kurniawan, Edi; Rahman, Md. Mehadi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
COVID-19 harms the implementation of learning at various levels, including at Islamic universities. Students at Islamic universities must use e-learning for several months until the COVID-19 outbreak ends. Students are also required to have Higher-Order Thinking Skills (HOTS) to solve problems. They are also required to have Pro-Environmental Behavior (PEB) related to COVID-19. Previous research has developed a Higher-Order Thinking Skills Assessment based on Environmental Problem (HOTS-AEP). The purpose of this research was to describe an implementation of e-learning, HOTS, and PEB on students during the COVID-19 outbreak. The method used was descriptive through the survey technique. This research was conducted in March 2020. The instruments used were questionnaires on e-learning and HOTS-AEP related to COVID-19 (HOTS-AEP-COVID-19). Meanwhile, to measure PEB, PEB-COVID-19 was used. All instruments were constructed using Google Form and were distributed to 137 respondents via social media. The results showed that the implementation of e-learning was generally effective (27.74%) and quite effective (43.07%) even though some problems were encountered. Other results showed that students’ HOTS were in the poor category (26.20) while the PEB was in the excellent category (84.82). it can be concluded that e-learning during the COVID-19 outbreak has gone well although some innovations are needed. Besides that, HOTS needs to be improved while PEB needs to be maintained.